HOW TO TRANSLATE NEOLOGISMS IN ENGLISH - Qozoqova Feruza Sevindikovna; Kenjayeva Mukhlisa Bakhodirovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT Neologisms are one layer of English vocabulary that is covered in this study. The definition of neologisms, the primary causes of new word creation, and the sources of these words—such as the Cambridge Dictionary, Oxford English Dictionary, Macmillan Dictionary, and Merriam Webster Dictionary—are all covered. The article describes the characteristics of neologisms and provides a detailed classification of them according to the process by which they are formed. For example, it lists phonological neologisms, borrowings, and morphological neologisms, which are formed by affixation, composition, conversion, and contraction. Furthermore, the authors highlight the difficulty of translating neologisms and provide a list of different approaches, including transcription, transliteration, calquing, and descriptive translation, each of which is explained and supported by an example drawn from one of the aforementioned sources.